Spatial Design of Hearing Aids Incorporating Multiple Vents - Daniel Stevenson; Grant Searchfield; Xun Xu (Trends in Hearing, 2014)
The main aim of this study was to investigate the shape variation in the human ear canal and the effects of venting on the spatial design of hearing aids. The second aim was to determine the design feasibility of a multiple venting hearing aid and assess the flexibility of design provided. A statistical shape model based on principal component analysis was created from a dataset of 60 left and 49 right ears. The modal variations of these models were then examined to determine the narrowest portion of the ear canal likely to limit effective venting. Finally, 3D models of two hearing aid shells, one with multiple 0.4-mm vents and the other with a single large 3-mm vent were created. Results showed that more than 50% of the shape variation in the human ear canal can be described by the first three modes of the statistical shape model developed. The narrowest predicted variation of this model had a minimum area of 36.4 mm 2 , and the mean ear shape was found to have a minimum area of approximately 48 mm 2 . It is estimated that even with a conservative vent packing of 0.4, multiple venting equivalent to at least a single 2-mm vent is achievable. The predicted variation in the human ear canal provides adequate physical space for a feasible multiple vented hearing aid shell. Furthermore, as multiple small vents are able to fit in around other components in the hearing aid design, certain design flexibility is provided by this venting approach.